The Effect of Earnings Management and Audit Quality on Company Value Creation With Risk as an Intervening Variable - Bramastyasa Gilang Pradata (Sean Institute, 2025)
The purpose of this study is to examine the effect between earnings management and audit quality on company value creation by considering risk taking as an intervening variable.For this purpose, this study uses research data from companies listed on the Indonesia Stock Exchange, especially in the Miscellaneous Industry from 2018 to 2020. The structural equation model using the WarpPLS program was used to analyze the data.The findings of this study indicate that earnings management has a negative impact on corporate risk taking. Then, audit quality has an influence on the company's risk taking. Meanwhile, if risk is considered to test firm value, the findings show that the three components of earnings management, audit quality and risk have an influence on the creation of company value creation.The results of this study are expected to help analyze capital markets in developing countries, as well as provide an overview of strategies that companies can use to create corporate value.